2013
DOI: 10.1177/1012690213507718
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent sport participation and alcohol use: The importance of sport organization and the wider social context

Abstract: This paper investigates the relationship between adolescent sport participation and alcohol use, focusing on differences in sport contexts. We also include the wider social context, the role of peers and parents as key variables in our analysis. Our sample consists of a nationally representative sample of 10,992 Icelandic adolescents. The findings indicate that adolescents that participate in formally organized sport clubs are less likely to use alcohol than those that do not. The results obtained for particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 46 publications
(82 reference statements)
3
25
0
3
Order By: Relevance
“…This finding is in line with previous research whereby the sports club offer an environment favourable for adopting a healthy lifestyle [2]. Halldorsson and colleagues [38] suggested taking part in sports clubs buffers overall alcohol use, particularly when alcohol consumption is contingent on having friends that consume alcohol.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in line with previous research whereby the sports club offer an environment favourable for adopting a healthy lifestyle [2]. Halldorsson and colleagues [38] suggested taking part in sports clubs buffers overall alcohol use, particularly when alcohol consumption is contingent on having friends that consume alcohol.…”
Section: Discussionsupporting
confidence: 82%
“…This study is part of the multidisciplinary Health Promoting Sports Club (HPSC) study conducted in Finland by the University of Jyväskylä with six sports and exercise medicine centres and the UKK Institute [38]. Participants aged between 14-16 years old from the 10 most popular sports in Finland were asked to participate in the study during 2013.…”
Section: The Sample and Data Collectionmentioning
confidence: 99%
“…lower) socio-economic neighborhoods. Further, in a study conducted with Icelandic secondary students, Halldorsson et al [ 126 ] compared alcohol use throughout adolescence in three different groups: adolescents involved in formally organized sport clubs (referred to as ‘organized sport’ in North America), those involved in informally organized sport activities, and those not involved in sport. Results revealed that youth who participated in formally organized sport clubs were less likely to use alcohol than those who did not participate in these clubs.…”
Section: Resultsmentioning
confidence: 99%
“…Participation in organized sports with a club or team was assessed with the question: ‘How often do you participate in sports with a club or a team?’ (1 = almost never, 2 = once per week, 3 = 2–3 times per week, 4 = 4–6 times per week and 5 = almost every day). It should be noted that sports teams in Iceland are area‐ and/or neighborhood‐based clubs, not school teams, and are supervised by responsible and well‐trained adults .…”
Section: Methodsmentioning
confidence: 99%
“…Every 3 years the ICSRA surveys, entitled ‘Youth in Iceland’ , focus on broad categories of interest . For the purposes of this report, those categories include: (a) substance use, where measurement is similar to the Monitoring the Future surveys being conducted in the United States and the ESPAD surveys in Europe ; (b) protective factors for substance use, with focus on factors that have been known to decrease the odds of substance use among teens, such as parental support, monitoring and co‐communication, school wellbeing and participation in constructive recreational and extracurricular activities such as organized sports ; and (c) risk factors for substance use such as unsupervised idle hours, party life‐style and peer substance use .…”
Section: Primary Prevention In Icelandmentioning
confidence: 99%